Lastne delnice ciljne družbe pri obvezni prevzemni ponudbi in obveščanju o pomembnih deležih - Šmigoc, Matej (Podjetje in delo, 2016)
The author discusses the influence of a target company's own shares on the shareholder's obligation to submit a mandatory takeover bid and to inform the company of achieving the threshold of significant interest. At the same time, in comparison with German law, the author exposes the problem of the independence of these shareholder's liabilities, from its actual control of the company, mainly because of a shareholder's inability to know the exact number of company's own shares at any time. He also discusses a Directive 2013/50/EU of the European Parliament and of the Council, which member states were obliged to transpose into their own legal order until 27 November 2015, and the consequences that the new legislation, with stricter sanctioning of non-compliance regarding obligations to inform a company about major holdings of voting rights, will have on shareholders of listed companies.
Keywords: delnice; delniške družbe; lastninska razmerja; prevzem